Association of thymolsulfonephthalein and cresolsulfonephthalein anions with cationic cyanines in aqueous solution - Shapovalov, Serghiy; Kiseliova, Yana (Publishing House of Lviv Polytechnic National University, 2010)
The formation of associates between one- or twocharged anions of sulfonephthalein dyes – thymolsulfonephthalein, cresolsulfonephthalein – and cyanine cations (pinacyanol, quinaldine red) has been considered in aqueous solution. Equilibrium association constants have been determined using spectrophotometric data. By semiempirical methods the enthalpy of formation and the eventual structure of ions and associates have been established. Розглянуто утворення у водному розчині асоціатів між одно- або двозарядними аніонами сульфо-фталеїнових барвників – тимолсульфофталеїну, крезолсульфофталеїну – і катіонами ціанінів (пінаціанол, хінальдиновий червоний). За допомогою спектрофотометричних даних визначено рівноважні константи асоціації. Напівемпіричними методами розрахована ентальпія утворення йонів і асоціатів, встановлено їх ймовірну будову.
Асоціація аніонів тимолсульфталеїна і крезолсульфофталеїна з катіонними ціанінами у водному розчині
Keywords: association; aqueous solution; thymolsulfonephthalein; cresolsulfonephthalein; enthalpy of formation; dyes; absorption spectra; асоціація; водний розчин; тимолсуль-фофталеїн; крезолсульфофталеїн; ентальпія утворення; барвники; спектри поглинання